(untitled) (Acta Polytechnica CTU Proceedings, 2017)
of the city of Perm (Russia). The monitoring results are presented for two experimental sites. Site 1 is characterized by dense urban development and related to type I soil conditions in Perm (the left-bank area of Perm). Site 2 is located in a low-urbanised region of the city and is related to type II soil conditions in Perm (the right-bank area of Perm).